Association of a national insurer's reference‐based pricing program and choice of imaging facility, spending, and utilization. (10th March 2020) - Sinaiko, Anna D.; Mehrotra, Ateev
Abstract: Objective: To examine the association of a national insurer's reference‐based pricing (RBP), program for outpatient advanced imaging—a benefit design to encourage patients to choose lower‐price facilities. Data Source/Study Setting: Administrative and medical claims data for three self‐insured employers that introduced RBP and a comparison group without RBP. Study Design: Difference‐in‐difference comparison of pre‐RBP (2014) and post‐RBP (2015‐6) care between intervention and comparison groups. Data Collection/Extraction Method: We identified 137 680 imaging procedures (4602 intervention group; 133 078 comparison group) in 2014‐2016. Principal Findings: In the first post‐RBP year (2015), there was no change in choice of facility; by the second year, RBP‐exposed enrollees were 21.9 pp (95% CI: 18.5, 25.3) more likely to choose a lower‐priced facility and net prices were 101.05 (95% CI: −130.65, −71.46), a difference of 8.1 percent lower. RBP was associated with higher patient out‐of‐pocket spending in the first post‐RBP year (31.82; 95% CI: 10.91, 52.73). There was no change in utilization, and higher‐priced providers did not lower prices in the postperiod. Net savings represented 0.3 percent of outpatient spending. Conclusions: Reference‐based pricing for advanced imaging was associated with a shift to lower‐priced facilities, but net impact on outpatient spending was modest. Patients paid increased out‐of‐pocket costs, though the amount declined after the first year of the program.